KAJIAN OPTIMALISASI PEMANFAATAN LAHAN DAN BANGUNAN KANTOR PEMERINTAH KABUPATEN KOTABARU KALIMANTAN SELATAN - Ruliana Febrianty (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The basic principle of a property assessment is a function of the use of the property. Discourse to move the land and buildings Kotabaru District Government Offices other regions to make land and buildings Kotabaru District Government Office that is currently left / not used anymore are not yet in the highest and best use, whereas strategic location in the center of town it is possible to optimize its use . Therefore takes over the function of land use and building the highest and best. The methods of this study are (1) Analysis of the determination of the alternative use of land and buildings by distributing questionnaires (2) Analysis of the estimated market value of land without development (3) Analysis of the estimated market value of land with development. From the analysis of several conclusions can be drawn the following: (1) 41 respondents provide results in the form of the proposal is to attempt to get a big enough response, the percentage of respondents fairly large hotel business at 53%. And the percentage of respondents to the classification of a 4 star hotel large enough that 56%. (2) optimal utilization of the land use and building principle of highest and best use is in zone I functioned as a hotel business with the classification 4, Land and buildings Kotabaru District Government Offices Zone II is for the use of land and buildings leased to private parties with alternative the use, namely: shops, offices, training centers (courses). Land and buildings Kotabaru District Government Offices Zone III is for land use and building public facilities such as gymnasium. Keywords : highest and best use, value, klasification